FAKTOR RESILIENSI KLIEN PEMASYARAKATAN DALAM PERSPEKTIF TEORI BIOEKOLOGI BRONFENBENNER: PENTINGNYA FAKTOR DUKUNGAN SOSIAL - aisyah nurul hafidah; Margaretha Margaretha (Psyche: Jurnal Psikologi, 2020)
The difficulties faced by parolee in social reintegration process can make them resort back to crime or recidivist. However, if individuals can adapt positively, correctional clients can achieve resilient conditions, hence, easier for them to stay out from crime The purpose of this study was to determine the protective factors and risk factors that influence resilience of parolee during the social reintegration process using the perspective of Bronfenbrenner's bioecological theory. This study was conducted on a sample of 131 adult parolee registered at Correctional Center Class I Surabaya. Data obtained using survey methods and using simple regression analysis methods. This study shows that the factors that influence resilience of parolee are factors that are in the microsystem layer, namely social support factors. Keywords: resilience, correctional clients, protective factor, risk factor